Non-linear interface thermal conditions in three-dimensional thermoelastic contact problems. (December 2020) - Ubero-Martínez, I.; Rodríguez-Tembleque, L.; Cifuentes-Rodríguez, J.; Vallepuga-Espinosa, J.
Highlights: A novel augmented Lagrangian formulation is proposed for 3D non-linear ITC. Thermal contact conductance models and interstitial convective conditions are studied. Influence of forced convection conditions and the presence of a CNT-based TIM are analyzed. Influence of forced convection conditions is important for great conductive interface conditions. Thermal conductance of the TIM is highly improved by the addition of CNT. Abstract: In this paper, a new and robust formulation to solve three-dimensional thermomechanical contact problems under non-linear interface thermal contact (ITC) conditions is presented. This methodology allows us to consider non-linear thermal contact conductance, including the presence of thermal interface materials (TIM), and convective conditions at the interstitial contact region. The Boundary Element Method (BEM) is assumed in order to compute the thermoelastic influence coefficients. The interface thermomechanical contact methodology is based on an augmented Lagrangian formulation where an efficient iterative Uzawa type scheme of resolution is proposed. The methodology is validated by comparison with benchmark solutions and later on, some additional examples are presented to study the influence of several ITC conditions, i.e., the presence of TIM doped with carbon nanotubes (CNT) and/or interstitial boundary conditions, in the thermoelastic contact variables (i.e., the contact area, the contact tractions, the temperature or the thermal flux distributions) of this kind of problems.